BIAS GENDER DALAM TRADISI TAHFIZ AL-QUR'AN: Pandangan Para Pegiat Tahfiz al-Qur'an tentang Peran Perempuan dalam Menjaga Transmisi al-Qur'an - Fatiyaturrahmah (An-Nisa’ Journal of Gender Studies, 2016)
Historical record showed the number of woman of companions of prophet who memorize Al-Qur'an. Historically, however, the tradition of giving chance to women to memorize Al-Qur'an did not continue in the next periods. Memorizing Al-Qur'an was claimed only for men. It can be seen that there is no woman perawi in Al-Qur'an in transmission system. In Indonesia, for instance, the chain of sanadlima figures of Al-qur'an memorizers become the main reference and has a role in the spread of tahfizul Qur'an that does not mention any of the female characters included in the chain. This study employs quantitative research using field research through feminist approach. Data is presented in verbal not numbers. The use of feminist approach was caused the lack of marginalization of women role in transmission system of tahfiz Al-qur'an which cannot release from unstable gender. The following are the result of the study. First, there is phenomenon of woman marginalization in Al-qur'an transmission system although man dominates it. In reality, Nyaiand Ustałzah who have pondok pesantren tahfiz listen called menyemak and educate tahfiz students. After they finish reciting Al-qur'an and memorizing it, Kyai will give the certificate. Second, the factors underlying the marginalization of al-Qur an transmission system states as follow. First, theologically, man is imam and woman is makmum. Moreover, since woman get menstruation, the religious experience became imperfect and less opportunity to dedicate in public. Sociologically and naturally, man memorizes faster than woman and he has more chance to join khataman and seaman. Third, the implementation of gender equality in tahfiz al-Qur'an culture has not been conducted yet.